Green governance and green clusters: regional & national policies for the climate change challenge of Central & Eastern Europe - Philip Cooke (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
This paper focuses on the climate change challenge faced by Central & Eastern European countries both those inside the European Union and those outside it. They have enormous energy intensity and associated greenhouse gas (GHG) emissions, mainly from energy production, which is oil, and worse, coal-fired power stations. As a group of blocs, CEE is a significant actor on the global climate change canvas. Their actions can make a difference. But there are numerous regulatory constraints that make this currently difficult. With the onset of a new global regime consequent on the renegotiation of acceptable levels of GHG emissions at Bali in 2007, to be ratified in Copenhagen in 2009, all countries with levels such a those in CEE will have to reduce emissions significantly as will countries throughout the world, especially the "big burners" like USA and China. With some data and textured case illustrations the article points the way to mitigation of emissions by learning from Denmark, the world leader as a "green economy" and Wales, part of the UK which has a long established heavy industry tradition comparable to many CEE countries and where positive change is underway from unlikely sources.
Keywords: A14; O33; R11; R58; 650; Green governance; Green innovation; Green clusters; Renewable energy; Wind turbines; Solar thermal energy; Biofuels